A comparison of risk and return for contract and independent hog finishing - Parcell, J.L.; Langemeier, Michael R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Risks associated with independent hog finishing have prompted producers to seek alternative production and marketing methods. A means of reducing risk has developed through contract hog finishing. Research results indicate that risk-neutral producers require contract base payments ranging from $11.25 to $14.00 per head. Strongly risk-averse producers require contract base payments ranging from $4.75 to $7.75 per head. The lower ends of the ranges are for a contract with performance incentives. The upper ends of the ranges are for a flat contract without performance incentives. Calculated required base payments are similar to those payments currently received by contract hog finishers.
Keywords: Swine; Risk management; Contract hog production